Measurement of space charge density distributions and dielectric resonance enhancement of beam deflection properties of KTN crystal - Pan Chen; Wendie Chen; Shuo Zhang; Jianwei Zhang; Jianxing Shen; Bing Liu; Xuping Wang (Journal of Materiomics)
In recent years, potassium tantalum niobate (KTN) electro-optical deflection devices have gained considerable attention because of their notable advantages, such as large deflection angles, low operational voltage requirements, and compact dimensions. This study uses the phase-shifted interferometric optical path to characterize the influence of direct current (DC) voltage on charge density. An interferogram is acquired using the four-step phase-shifting technique, enabling the calculation of phase delays and deducing the variation in charge density. Experimental results demonstrate that the charge density near the cathode increases with an increase in DC voltage. Subsequently, we utilize the frequency dependence of the dielectric constant of the KTN crystal on the electric field. The dielectric constant can be enhanced when the characteristic frequency of the motion of the polar nanoscale region matches the frequency of the electric field. This field-induced enhancement effect improves the beam deflection performance of the KTN crystal. Application requirements in the field of high-speed random scanning can be realized through the mechanism of the KTN crystal co-acting with DC and alternating current electric fields.